2020
DOI: 10.1016/j.ejon.2020.101823
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of decrements in physical and cognitive function is common in older oncology patients receiving chemotherapy

Abstract: Purpose: Older adults receiving cancer chemotherapy are at increased risk for decrements in physical (PF) and cognitive (CF) function.Objectives: Study identified subgroups of patients with distinct PF and CF profiles; risk factors associated with subgroup membership; and impact of subgroup membership on quality of life (QOL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…59 Of note, although neither the subjective nor objective measures of physical function were associated with changes in cognitive function, in a previous study of older breast cancer patients, 12 higher levels physical function decreased the odds of long-term cognitive decline and that an accelerated cognitive decline was associated with decrements of physical function. In addition, in our previous study with a different sample, 63 more than 50% of the older patients had decrements in physical and cognitive function over 2 cycles of chemotherapy. Given our relatively small sample size and the known associations between physical and cognitive function, 22,23,25,27,28 future studies with larger samples need to evaluate the relative contribution of physical function to changes in cognitive function in older oncology patients.…”
Section: Discussionmentioning
confidence: 76%
“…59 Of note, although neither the subjective nor objective measures of physical function were associated with changes in cognitive function, in a previous study of older breast cancer patients, 12 higher levels physical function decreased the odds of long-term cognitive decline and that an accelerated cognitive decline was associated with decrements of physical function. In addition, in our previous study with a different sample, 63 more than 50% of the older patients had decrements in physical and cognitive function over 2 cycles of chemotherapy. Given our relatively small sample size and the known associations between physical and cognitive function, 22,23,25,27,28 future studies with larger samples need to evaluate the relative contribution of physical function to changes in cognitive function in older oncology patients.…”
Section: Discussionmentioning
confidence: 76%
“…While the exact relationships between various brain functions and gait are not well understood, research suggests that higher levels of CF and memory are needed to organize mobility [41]. In addition, a prior study of older adults found associations between CF and PF [42]. As noted in one review [41], compared to other age-related changes, a decrease in gray matter had the strongest association with poorer gait.…”
Section: Discussionmentioning
confidence: 95%